Frequency and Outcome of Full Term Pregnant Patients with Previous Cesarean Section - Shazia Naseeb, Fouzia Bibi, Shaista Rashid, Beena Barkat Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the frequency of repeat Cesarean Section in patients with previous one cesarean section To compare the maternal and perinatal outcome in vaginal birth after Cesarean and repeat caesarean section Material and Methods: This Cross sectional study was conducted at Obstetrics & Gynecology unit1 JPMC Karachi from Jan 2020 to31 Dec2020.A total of 137 women with history of previous one cesarean section were included in this study. All patients’ history and examination was taken. The data was collected on a predesigned Performa. Mean and Standard Deviation for quantitative variables and percentage for categorical qualitative variables. Maternal and perinatal outcomes was compared between women who have VBAC and those who have repeat Cesarean section by using chi-square test with P-values less than or equal to 0.05 significant. Results: The average age of the women was 29.88±3.26 years. Frequency of repeat caesarean section in patients with previous one cesarean section was 52.55%. PPH was observed in 37.96% cases while prolong hospital stay in 28.47%. There were 15.33% still birth, Apgar score less than 7 in 42.34% at 1 minute, and NICU admission was observed in 23.38%. Rate of Postpartum hemorrhage and prolong hospital stay was significantly high in repeated caesarean section. Conclusion: All of the maternal and prenatal outcomes were significantly high in repeated Cesarean section as compare to vaginal deliveries. The trial of labor in women with a single previous caesarean delivery can safely reduce rate of caesarean section.